The Spirit of Capitalism According to the Michelin Company Anthropology of an Industrial Myth - Védrine, Corine (Palgrave Studies in Urban Anthropology,, 2019)
The city of Clermont-Ferrand in central France is inextricably linked to the global tire company Michelin-not only by the industrial, social, and economic realities that tie employees to employer, but also by a multi-generational, regional belief in the company's entrepreneurial mythos, the so-called "Michelin spirit." Since the 1980s, transformations in capitalist systems have challenged the Michelin ideology: the end of corporate paternalism, the reduction of the work force, and a new wave of managers have left employees in the region feeling the sting of abandonment. Even in the face of these significant changes, however, the ethnographic enquiry at the heart of this book testifies to the enduring strength of the "spirit of capitalism": even as the bonds between employees, companies, and their regions are undergoing significant transformation, entrepreneurial myths endure-in part in fear of the end of a secure, organizing structure. .